Dissociation Between the Epileptogenic Lesion and Primary Seizure Onset Zone in the Tetanus Toxin Model of Temporal Lobe Epilepsy - Chvojka, J; Kudláček, J; Liska, K; Pant, A; Jefferys, J Gr; Jiruska, P (Physiological research, 2024)
Despite extensive temporal lobe epilepsy (TLE) research, understanding the specific limbic structures' roles in seizures remains limited. This weakness can be attributed to the complex nature of TLE and the existence of various TLE subsyndromes, including non-lesional TLE. Conventional TLE models like kainate and pilocarpine hinder precise assessment of the role of individual limbic structures in TLE ictogenesis due to widespread limbic damage induced by the initial status epilepticus. In this study, we used a non-lesional TLE model characterized by the absence of initial status and cell damage to determine the spatiotemporal profile of seizure initiation and limbic structure recruitment in TLE. Epilepsy was induced by injecting a minute dose of tetanus toxin into the right dorsal hippocampus in seven animals. Following injection, animals were implanted with bipolar recording electrodes in the amygdala, dorsal hippocampus, ventral hippocampus, piriform, perirhinal, and entorhinal cortices of both hemispheres. The animals were video-EEG monitored for four weeks. In total, 140 seizures (20 seizures per animal) were analyzed. The average duration of each seizure was 53.2+/-3.9 s. Seizure could initiate in any limbic structure. Most seizures initiated in the ipsilateral (41 %) and contralateral (18 %) ventral hippocampi. These two structures displayed a significantly higher probability of seizure initiation than by chance. The involvement of limbic structures in seizure initiation varied between individual animals. Surprisingly, only 7 % of seizures initiated in the injected dorsal hippocampus. The limbic structure recruitment into the seizure activity wasn't random and displayed consistent patterns of early recruitment of hippocampi and entorhinal cortices. Although ventral hippocampus represented the primary seizure onset zone, the study demonstrated the involvement of multiple limbic structures in seizure initiation in a non-lesional TLE model. The study also revealed the dichotomy between the primary epileptogenic lesion and main seizure onset zones and points to the central role of ventral hippocampi in temporal lobe ictogenesis.
Keywords: tetanový toxin; záchvaty; Rats; Electroencephalography; potkani Sprague-Dawley; hipokampus; Epilepsy, Temporal Lobe; Disease Models, Animal; mužské pohlaví; elektroencefalografie; epilepsie temporálního laloku; Seizures; krysa rodu Rattus; modely nemocí na zvířatech; Tetanus Toxin; zvířata; Rats, Sprague-Dawley; Male; Hippocampus; Animals